Estudio de la influencia del comercio informal en el desarrollo socio económico del cantón Bolívar - Giler Calderón, Ingrid Elizabeth (2012)
This thesis is the synthesis of the study of the influence of the Informal Trade in the socioeconomic development of the Cantón Bolívar; the problem was identified, the authors propose as general objective: To determine the influence of the Informal Trade in the socioeconomic development of the Cantón Bolívar; and, their specific objectives: To diagnose the situation of the Informal Trade in the Cantón Bolívar; to know the causes, advantages and disadvantages of the Informal Trade; to identify the economic sectors related with the Informal Trade; to measure the level of preparation of the Informal Merchants; and to measure the level of revenues of the Informal Merchants. To carry out the execution of these objectives a survey it was applied the Informal Merchants in the City of Stocking. Their realization collaborated for the cash study of the current situation of the Informal Trade of the canton Bolivar and its influence in the socioeconomic development; reflecting that 163 of people interviewed with of the masculine gender, of which 96 have studied the secondary level and 126 of them are of married civil state. 96 of them take in this business more than 12 years. 197 don't possess Unique Registration of Taxpayers and they work therefore to the margin of the Law they don't emit Vouchers of Sale, neither they declare the Tax to the Rent neither the Tax to the Added Value; 158 carry out this activity like only occupation. Another of the opposing details is that 137 have a similar entrance to the Basic Salary, they don't have hired any person, therefore they are not assured to the IESS; they carry out this activity in the public road and they are the economic support of their family. 110 of them also considered that the yield of this activity is good; among the main products that the Informal Merchants negotiate 66 they negotiate Foods, 54 several, 22 Clothes with an investment not bigger to $500 dollars.